The Decline of Traditional Learning Methods in Changing Indonesia: Trends of Bandongan-Kitāb Readings in Pesantrens - Nurtawab, Ervan (Studia Islamika, 2019)
This article examines the marginalization of the traditional pesantren educational system and how the system finds a way to be recognized as equal in contemporary Indonesia. This study is mainly based on the author’s observation of practices in Tafsīr al-Jalālayn pedagogies in traditional and modern West Javanese pesantrens and the kitāb reading tournament, with in-depth interviews of some related figures and teachers, during the periods 2015-2017. This article argues that the marginalization of the educational system since the coming of modernization in the early twentieth century continues to happen up to the end of the century. The graduates of the traditional institutions keep left behind, and that the traditional pesantren system is merely recognized as a type of non-formal education. The twenty-first century period witnessed attempts from the Indonesian government through the Ministry of Religious Affairs to equalize the kitāb-based learning in the traditional milieu. By so doing, the graduates are expected to receive equal rights for pursuing their education or looking for a career.